Cancer pain patients do not successfully handle opioids - Kosev, Liel; Morag, Ofir; Levitan, Michelle; Goor-Aryeh, Itay (Journal of Opioid Management, 2024)
Objective: To evaluate patterns of opioid handling as well as their associated variables. Design: A transversal study. Setting: Institutional care. Participants: One hundred cancer pain patients aged 18 and above at diagnosis. Interventions: Open and dichotomous questions related to opioid handling and a depression-anxiety scale. Main outcome measure(s): The percentage of patients who properly handled opioids. Results: Of those surveyed, 42.1 percent of patients reported receiving opioid storage instructions, 73 percent did not receive any instructions related to proper opioid return/disposal, and 39 percent wrongly discarded them. The mean of patients with anxiety symptoms was 6.95 and of depression symptoms was 8.19. The Hebrew Version of the Hospital and Anxiety Scale total mean was 15.1. A significant relationship among patients with poor disposal habits was also found. Conclusions: Despite being aware of opioid’s danger, patients’ attitudes evidenced a poor safety responsibility. We believe that this might be due to the high percentage of disinformation and the influence of psychological symptoms on patients’ decision-making.